Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada CV Babelmart Tanjungpandan - Januarika, Zahra Aulya; BP, Dwi Windradini; Mastika, I Ketut; Kuncoro, Setyo (Jurnal Strategi dan Bisnis, 2024)
The purpose of this research is to analyze the influence of work discipline and the work environment on employee performance at CV Babelmart Tanjungpandan. The study is conducted with the intention of gaining an understanding of the factors that impact employee performance, and optimizing employee performance is crucial as it aids in achieving the company's goals. The applied method is quantitative, using a questionnaire as the research instrument. The research population consists of 42 individuals, and a sample of 38 people is obtained using the Slovin formula with a 5% margin of error. The subjects work in the retail department of CV Babelmart Tanjungpandan. Multiple linear regression analysis is applied to the collected data to test hypotheses. The research reveals that work discipline has an impact of 63.2%, the work environment influences by 59.1%, and collectively, the work environment along with work discipline have a simultaneous impact on employee performance of 78.7%. Keywords: work discipline, work environmeent, employee performance